Piezoelectric energy harvesting from beam vibrations induced by an aerodynamic force generated by a fluctuating wind - Zemtchou, Francis Rolphe; Mabekou Takam, Jeanne Sandrine; Louodop Fotso, Patrick Hervé [UNESP]; Talla, Pierre Kisito (Elsevier, 2025)
The study of wind-induced piezoelectric energy harvesting is carried out in this work. The energy harvesting device consists of a cantilever beam with a tip mass. This tip mass is subjected to the action of a wind whose speed has a steady part and a sinusoidal fluctuation. The Euler–Bernoulli beam theory associated with Kirchhoff's laws allows to obtain the electromechanical equations describing the dynamics of the system. The results show an increase in electrical power with the amplitude of fluctuations in wind speed, as well as with the increase in the tip mass. This fluctuation also allows to obtain a wide operational frequency band. In addition, the increase in the intensity of the fluctuation is accompanied by the appearance of chaotic behaviors, crisis and intermittency phenomena.
Keywords: Aerodynamic force; Cantilever beam; Crisis; Energy harvesting; Piezoelectric